An econometric analysis of South African monetary phenomena - Hurwitz, A M (School of Economics, 2015)
Monetarism, and more particularly, the Monetary approach to the balance of payments has been the subject of important theoretical debate and empirical research over the last twenty years, and has assumed particular relevance in the world inflationary impasse of the present day. Although of great relevance to South Africa, the theory has received comparatively little attention locally and statistical studies are rare.